ANALISIS SISTEM DAN PROSEDUR KREDIT KEPEMILIKAN RUMAH (KPR) DENGAN AKAD PEMBIAYAAN MURABAHAH PADA PT. BANK BRI SYARIAH CABANG MEDAN - Heriyati Chrisna; Agita Karin; Hasrul Azwar Hasibuan (Jurnal Akuntansi Bisnis dan Publik, 2020)
This study aims to determine how the system and procedures for giving home ownership loans (KPR) at PT. Bank BRI Syariah Medan Branch, and To find out whether home ownership loans (KPR) at PT. Medan Branch BRI Syariah Bank has / has not been in accordance with murabahah financing agreement with MUI DSN Fatwa No.04 / DSN-MUI / IV / 2000. This research method uses a qualitative descriptive approach which is a way to understand the related phenomena by providing a detailed understanding of the phenomenon. This study only analyzes the system and procedures for mortgage loans with murabahah financing contracts and is completed by conducting interviews directly with five (5) employees in the Account Officer PT. Bank BRI Syariah Medan Branch regarding the System and Procedure for implementing Home Ownership Loan to strengthen the results of the research. The results of this study indicate that the system and procedures for home ownership loans with murabahah financing contracts at PT. Bank BRI Syariah Medan Branch, gave a decision to evaluate the application for home ownership loans with the 5C principle as a basis for consideration. The next stage is, the procedure for KPR financing, analysis of KPR applications, approval of KPR financing applications, disbursement of KPR financing applications, and monitoring of repayment of KPR financing for which all KPR systems and procedures have been arranged and are in accordance with MUI DSN Fatwa No.04 / DSN- MUI / IV / 2000.